2020
DOI: 10.1159/000511009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Two Inspiratory Muscle Training Protocols, Low Loads versus High Loads, in Institutionalized Elderly Women: A Double-Blind Randomized Controlled Trial

Abstract: <b><i>Background:</i></b> Aging results in a decline in the function of the respiratory muscles. Inspiratory muscle training is presented as a possible solution to attenuate the loss of respiratory function in the elderly. The objective of the study was to evaluate and compare the efficacy of 2 protocols with inspiratory muscle training (IMT), low loads and high loads, to improve respiratory strength, functional capacity and dyspnea in institutionalized elderly women, over 65 years. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The improvement in MIP in the experimental group lasted for 6 months after surgery as presented in the follow up which provide evidence about the effectiveness of IMT on improving inspiratory muscle strength. This study come online with the previous study by Martin-Sanchez et al [33], who reported that high load of IMT (40%MIP) achieved higher improvement in the MIP than lower load IMT (20%) in institutionalized elderly women after 8 weeks of training.…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…The improvement in MIP in the experimental group lasted for 6 months after surgery as presented in the follow up which provide evidence about the effectiveness of IMT on improving inspiratory muscle strength. This study come online with the previous study by Martin-Sanchez et al [33], who reported that high load of IMT (40%MIP) achieved higher improvement in the MIP than lower load IMT (20%) in institutionalized elderly women after 8 weeks of training.…”
Section: Plos Onesupporting
confidence: 83%
“…The improvement of MIP in the experimental group can be explained by improved inspiratory muscle strength and endurance induced by IMT due to improving the neuromuscular recruitment pattern resulting from repeated exposure to the same task (additional resistance to the inspiration process) [33]. Thus, IMT improves the inspiratory muscle strength leading to improving oxygenation and reduce the risk of developing PPC, the length of hospital stay and the cost of hospitalization consequently.…”
Section: Plos Onementioning
confidence: 94%
“…In another study performed among Czeck subjects, Hubacek and colleagues found no significant difference in the frequency of Apo E alleles in 408 SARS CoV-2 PCR-positive subjects compared to the general population. However, when they compared symptomatic and asymptomatic COVID-19 subjects separately with the control population, they found a significant difference in the frequency of the Apo E4 allele between symptomatic patients and the control groups ( Hubacek et al, 2021 ). Given that our COVID-19 subjects were symptomatic patients the results obtained by Hubacek and colleagues might not be in real contradiction to our results, as they found a significant difference when compared the symptomatic group of their COVID-19 subjects to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE protein is a multi-faceted protein that has been found associated with many diseases ( Smith, 2000 ). Several studies have been performed to reveal a possible association between Apo E polymorphism and COVID-19 acquisition and severity ( Kuo et al, 2020b ); including few experimental studies ( Hubacek et al, 2021 ) and the current study would be one of that few.…”
Section: Discussionmentioning
confidence: 99%
“…An interval of about 1 min was allowed between the measurements to avoid short-term fatigue for respiratory muscles. The highest of 2 reproducible values was considered in the data analysis [26]. The advantage of this test is that it is a quick and noninvasive way to assess the strength of the inspiratory muscles through the PI max .…”
Section: Methodsmentioning
confidence: 99%